2017
DOI: 10.1002/maco.201709648
|View full text |Cite
|
Sign up to set email alerts
|

Tribocorrosion behavior of nickel aluminum bronze in seawater: Identification of corrosion‐wear components and effect of pH

Abstract: This work is focused on the influence of solution pH on the tribocorrosion behavior of a tribosystem between nickel aluminum bronze (NAB) and Al 2 O 3 . To explore the interaction mechanism between wear and corrosion, a pin-on-disc tribometer equipped with a potentiostat was used and the frictional, electrochemical responses were reported in situ during tribocorrosion processes as a function of the solution pH. Results revealed that a high pH solution would aggravate corrosion and give rise to accelerated mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In one, it was reported that increasing electrolyte pH adversely influenced tribocorrosion response. 121 Corrosion and wear were found to be linked and reinforced each other, leading to higher total tribocorrosion mass loss under experimental conditions. The passive film on the NAB alloy was damaged due to wear, and irregularities such as asperities resulting from induced-plastic deformation made the alloy surface more susceptible to corrosion.…”
Section: Corrosion Behavior Of Conventional Nab Alloysmentioning
confidence: 90%
See 3 more Smart Citations
“…In one, it was reported that increasing electrolyte pH adversely influenced tribocorrosion response. 121 Corrosion and wear were found to be linked and reinforced each other, leading to higher total tribocorrosion mass loss under experimental conditions. The passive film on the NAB alloy was damaged due to wear, and irregularities such as asperities resulting from induced-plastic deformation made the alloy surface more susceptible to corrosion.…”
Section: Corrosion Behavior Of Conventional Nab Alloysmentioning
confidence: 90%
“…In the context of tribocorrosion of NABs, the mass loss increased with higher pH values (ranging from 3.2 to 10.2) 121 and lower chloride concentration. 123 As a result, chloride-free solution resulted in the highest mass loss compared to chloride-containing solutions, which was correlated to the lubricating effect of electrolytes in the presence of Cl − ions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B.-B. Zhang et al 11,12 showed that selective corrosion is highly dependent on the pH and a corrosion wear mechanism was proposed, concluding that the tribocorrosion behavior of NAB alloy in seawater is closely related to the halide-ion concentration.…”
Section: Introductionmentioning
confidence: 99%